Tracking Seasonal Fluctuations in Land Water Storage Using Global Models and GRACE Satellites. Issue 10 (16th May 2019) - Scanlon, B. R.; Zhang, Z.; Rateb, A.; Sun, A.; Wiese, D.; Save, H.; Beaudoing, H.; Lo, M. H.; Müller‐Schmied, H.; Döll, P.; van Beek, R.; Swenson, S.; et al.
Abstract: Seasonal water storage fluctuations are critical for evaluating water scarcity linked to climate forcing and human intervention. Here we compare seasonal changes in land total water storage anomalies using seven global hydrologic and land surface models (WGHM, PCR‐GLOBWB, and five GLDAS models) to GRACE satellite data in 183 river basins globally. This work builds on previous analysis that focused on total water storage anomaly trends. Results show that most models underestimate seasonal water storage amplitudes in tropical and (semi)arid basins and land surface models generally overestimate amplitudes in northern basins. Some models (CLM‐5.0 and PCR‐GLOBWB) agree better with GRACE than others. Causes of model‐GRACE discrepancies are attributed to missing storage compartments (e.g., surface water and/or groundwater) and underestimation of modeled storage capacities in tropical basins and to variations in modeled fluxes in northern basins. This study underscores the importance of considering water storage, in addition to water fluxes, to improve global models. Plain Language Summary: We are relying more and more on global models to understand the water cycle, but we need to assess the reliability of model output. In this study we compare seasonal amplitudes in land total water storage from global models with those from GRACE satellite data in river basins globally. We found that seasonal amplitudes in total water storage account for more than half of the total signal, except in semiarid basins. Seasonal amplitudes are highest in tropical basins and lowest in semiarid basins. Some models agree better with GRACE than others (CLM‐5.0 and PCR‐GLOBWB). Most models underestimate GRACE‐derived seasonal amplitudes in tropical and semiarid basins but overestimate seasonal amplitudes in northern high latitude basins. The main cause of the discrepancies in tropical basins is likely insufficient storage capacity and lack of surface water inundation to accommodate the large seasonal storage variations. In northern high latitude basins, differences in snow physics and evapotranspiration increase seasonal amplitudes in water storage in newer versions of land surface models, overestimating GRACE‐derived seasonal amplitudes and reducing agreement with GRACE relative to earlier versions. Reliable models of seasonal variations in water storage are critical for assessing water scarcity, estimating response to climate extremes, and managing water resources. Key Points: Modeled seasonal amplitudes are underestimated in tropical and semiarid basins and overestimated in northern basins relative to GRACE Model‐GRACE discrepancies are attributed to insufficient storage capacities in tropical basins and biases in fluxes in northern basins This study highlights the value of using water storage, in addition to traditional water flux, in assessing and improving global models